Exploring the relationship between holistic spirituality and gender essentialism among Swiss university students - Zemp, Annika (Social compass, 2019)
Do women and men with stronger spiritual beliefs, experiences, and practices tend toward more or less ambivalent sexism and self-stereotyping? To shed more light on this issue at the intersection of religion and gender, we will analyze a survey of 379 Swiss university students, both women and men, to establish whether a positive or negative relationship between holistic spirituality and gender essentialism is empirically more plausible. Our data show a gender gap: women express stronger spiritual beliefs and they report on more spiritual experiences and practices than men. We also find, inter alia, associations between religious orientation and holistic spirituality as well as spiritual beliefs and ambivalent sexism for both women and men; yet, stronger spiritual beliefs are correlated with less self-stereotyping for men but with more self-stereotyping for women. In sum, our results tend to support a positive relationship between holistic spiritualty and gender essentialism.